(untitled) (International Journal of Food and Nutritional Sciences, 2025)
This study evaluates the suitability of soils along the Warri–Sapele Highway in Nigeria for subgrade road construction using Atterberg Limits and California Bearing Ratio (CBR) tests. Road failure and premature deterioration in this region have raised concerns about subgrade material quality. Soil samples were collected from multiple locations along the highway and subjected to standard geotechnical tests. Results revealed that a significant portion of the soils fall below recommended thresholds for subgrade performance, with high plasticity indices and low CBR values indicating weak bearing capacity and poor stability under load. The findings underscore the critical role of proper subgrade evaluation in preventing road failures and guiding infrastructure development in similar geotechnical settings.